Analisis Hubungan Antara Infrastruktur dan Kualitas SDM terhadap Daya Saing Ekonomi di Provinsi Jawa Tengah - Mindy Mindy; M. Afdal Samsuddin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the influence of infrastructure and the quality of human resources (HR) on economic competitiveness in Central Java Province. In the era of globalization, competitiveness is an important indicator of regional progress. Infrastructure such as transportation, electricity, and digital connectivity support economic efficiency, while quality human resources increase productivity and innovation. Despite their importance, development imbalances remain a challenge in Central Java. This study uses panel data from BPS and is analyzed using the Fixed Effect Model (FEM) method based on Chow and Hausman tests. The results show that together, infrastructure and human capital have a significant effect on economic competitiveness. However, separately, both have a negative and insignificant influence, with regression coefficients of -0.000195 for infrastructure and -0.0176 for human capital. The Adjusted R-squared value of 0.3149 indicates that 31.49% of the variation in competitiveness is explained by these two variables. This finding is important for determining the direction of future regional development policies.